COMPARATIVE ASSESSMENT OF COMPETENCE LEVEL OF TRANSPORT SYSTEM EXPERTS - AMBROSI, Grigore (Journal of Engineering Science (Chişinău), 2021)
The paper deals with the comparative assessment of competence level of transport system experts. The high level of competence of the experts is the premise to ensure the quality of the expertise of the systems insufficiently formalized from a mathematical point of view and characterized with a high degree of uncertainty. Six factors for assessing the competence of transport system experts were summarized. The values of the priority vector of the competence factors were established with the application of the Saaty algorithm and scale in nine points by the method of comparisons in pairs. The value of the concordance ratio of the experts' opinion for the prioritization matrix was calculated. The comparative competence coefficient of the experts in transport systems was calculated and the hierarchy of experts was established according to the value of the nominal coefficient.